The origin of vein-type copper-lead-zinc deposits Host in Palaeozoic metamorphic rocks at the Southeast Anatolian Orogenic Belt (Kupluce-Adiyaman, Southeastern Turkey) - Akyildiz, Mustafa; Yildirim, Nail; Goren, Burcu; Yildirim, Esra; Ilhan, Semiha (Pergamon-Elsevier Science Ltd, 2015)
The study area is located around the town of Kupluce between the celikhan and Sincik districts (Adiyaman, Turkey). Mineralisations are located at the Southeast Anatolian Orogenic Belt. Despite many differential units, especially in age and lithology, that coexist in the region, mineralisation and alteration are only developed in partly concordant/partly disconcordant veins/veinlets of quartz within chlorite schists, sericite schists, mica schists/mica gneisses, quartz schists and metadiabases of the Palaeozoic Puturge metamorphics. Pyrite, chalcopyrite and sphalerite are dominant minerals in mineral paragenesis. Chalcocite, covellite and carollite are also found in trace amounts. Quartz, calcite, sericite and chlorite are the gang minerals. Silicification, sericitisation, chloritisation, epidotisation and limonitisation are widespread in limited areas around ore veins. The estimated Co/Ni (1.8-43) ratio in pyrites belonging to mineralisation deposits indicates that mineralisation in the region is related to magmatic hydrothermal deposits. In addition, REE (rare earth element) contents of mineralisation deposits in chondrite-normalised diagrams are enriched and show a similar trend to that of chondritic values. This indicates that metals that form mineralisation deposits are related to magmatic rocks. Values of delta S-34 estimated in the Kupluce region vary between 1.6 parts per thousand and 2.34 parts per thousand. Values of delta S-34 close to 0 indicate that the sulphur forming the mineralisation is of magmatic origin. In addition, delta O-18 values vary between 8 parts per thousand and 10.8 parts per thousand and are consistent with magmatic water. Analyses of the fluid inclusions in quartz samples from mineralisation deposits were performed, and the homogenisation temperature was estimated to be between 90 and 150 degrees C. These temperature values can be explained by the mixing of a solution with surface water. It was determined that mineralisation deposits were vein-type hydrothermal deposits that had developed due to Middle Eocene acidic-intermediate intrusions intersecting Palaeozoic-aged Puturge metamorphics, and that they exhibited similar characteristics to other mineralisation deposits observed along the Southeastern Anatolian Orogenic Belt. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Southeast Anatolian; Vein type Cu-Pb-Zn; Kupluce/Adiyaman; Metamorphic rocks; Isotope